Subcritical contact process seen from the edge: convergence to quasi-equilibrium - Andjel, Enrique (2016)
The subcritical contact process seen from the rightmost infected site has no invariant measures. We prove that nevertheless it converges in distribution to a quasi-stationary measure supported on finite configurations.